2015
DOI: 10.1088/1054-660x/25/3/035201
|View full text |Cite
|
Sign up to set email alerts
|

Impact of incoherent pumping field and Er3+ion concentration on group velocity and index of refraction in an Er3+-doped YAG crystal

Abstract: The effect of Er 3+ ion concentration and incoherent pumping field on the refractive index and group index in an Er 3+ : YAG crystal is investigated. It is shown that under different concentrations of Er 3+ ion in the crystal, the index of refraction and absorption can be changed and a high index of refraction is accompanied by amplification in the medium. Also, it is shown that with the switching from subluminal to superluminal, or vice versa, light propagation can be obtained by different concentrations of E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…A pivotal requirement is the interaction between a light source and a material, which can span across diverse mediums [13][14][15][16][17][18][19]. When an atom engages with a field, the resulting atomic coherence emerges as a crucial mechanism, facilitating effective control and modulation of the optical properties within quantum systems [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…A pivotal requirement is the interaction between a light source and a material, which can span across diverse mediums [13][14][15][16][17][18][19]. When an atom engages with a field, the resulting atomic coherence emerges as a crucial mechanism, facilitating effective control and modulation of the optical properties within quantum systems [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Many research groups have researched quantum coherence and interference phenomena in recent decades because of their possible implications in quantum information technology and all-optical developing systems [1][2][3][4][5]. In this instance, various groups have discussed regulating the group velocity of transmitted light from different media because of its possible use in quantum information processing [6][7][8][9][10]. It has been demonstrated that by varying a few controllable system parameters, the group velocity of the probe light may be altered between superluminal and subluminal light propagation.…”
Section: Introductionmentioning
confidence: 99%
“…The properties of GH shifts in transmitted and reflected light in a fixed structure by quantum coherence and interference effects have been investigated [10, 11-13, 16, 20, 21, 23-27]. The effect of quantum coherence and interference on optical properties of many systems due to applications in optical and quantum communication has been discussed [28][29][30][31][32][33][34][35][36][37][38][39][40][41]. For the first time, Wang et al [23] investigated the role of the quantum coherence effect on GH shifts of light beams in a fixed structure doped with a two-level atomic system.…”
Section: Introductionmentioning
confidence: 99%